2014
DOI: 10.1097/prs.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue–Derived Stromal Cells Inhibit TGF-β1–Induced Differentiation of Human Dermal Fibroblasts and Keloid Scar–Derived Fibroblasts in a Paracrine Fashion

Abstract: The authors show that adipose tissue-derived stromal cells inhibit TGF-β1-induced adverse differentiation and function of adult human dermal fibroblasts and TGF-β1-induced contraction in keloid scar-derived fibroblasts, in a paracrine fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 41 publications
2
68
2
Order By: Relevance
“…The comparative C t method (2 −ΔΔ C t ) was used to quantify gene expression levels where ΔΔ C t = Δ C t (sample) – Δ C t (reference). The previously validated reference gene beta‐2‐Microglobulin ( B2M ) was used to normalize samples . Primers to amplify fibronectin 1 ( FN1 ) , smooth muscle actin ( ACTA2 ), collagen type III alpha 1 ( COL3A1 ), collagen type I alpha 2 ( COL1A2 ), matrix metallopeptidase 1 ( MMP1 ), yes‐associated protein 1 ( YAP1 ) , tafazzin ( TAZ ), and plasminogen activator inhibitor 1 ( SERPINE1 ) were designed using Primer3 software, based on horse sequences found in the National Center of Biotechnology Information (NCBI) GenBank.…”
Section: Methodsmentioning
confidence: 99%
“…The comparative C t method (2 −ΔΔ C t ) was used to quantify gene expression levels where ΔΔ C t = Δ C t (sample) – Δ C t (reference). The previously validated reference gene beta‐2‐Microglobulin ( B2M ) was used to normalize samples . Primers to amplify fibronectin 1 ( FN1 ) , smooth muscle actin ( ACTA2 ), collagen type III alpha 1 ( COL3A1 ), collagen type I alpha 2 ( COL1A2 ), matrix metallopeptidase 1 ( MMP1 ), yes‐associated protein 1 ( YAP1 ) , tafazzin ( TAZ ), and plasminogen activator inhibitor 1 ( SERPINE1 ) were designed using Primer3 software, based on horse sequences found in the National Center of Biotechnology Information (NCBI) GenBank.…”
Section: Methodsmentioning
confidence: 99%
“…43,44 Previous research in our laboratory showed that ASC secrete paracrine factors that abrogate TGF-β-induced differentiation of dermal fibroblasts to myofibroblasts which is a mesenchymal transition too. 45 In general, ASC and their secreted bioactive factors harbour pro-regenerative [46][47][48] and anti-inflammatory potential. 49,50 In addition, ASC promote angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies done with full thickness wounds have shown that the knockdown of YAP and TAZ significantly delays the rate of wound closure and reduces the amount of TGF‐β1 expression in fibroblast cells . These factors also modulate the expression of TGF‐β1 signaling pathway components, such as Smad2 and Smad7 . Specifically, YAP is capable of interacting with Smad7 to enhance its ability to inhibit the TGF‐β pathway .…”
Section: Hypertrophic Scar Developmentmentioning
confidence: 99%
“…While the role of exposed fat tissue and inherent MSCs/ADSCs in burn wound healing is not yet completely understood, therapy with exogenous stem cells has been explored as a new promising modality of fibrosis/scarring/contracture prevention and treatment . MSCs are defined as self‐renewing multipotent stem cells that can differentiate into various lineages of mesenchymal origin .…”
Section: Hypertrophic Scar Developmentmentioning
confidence: 99%